Freestanding and Sandwich‐Structured Electrode Material with High Areal Mass Loading for Long‐Life Lithium–Sulfur Batteries. Issue 11 (6th January 2017) - Yu, Mingpeng; Ma, Junsheng; Xie, Ming; Song, Hongquan; Tian, Fuyang; Xu, Shanshan; Zhou, Yun; Li, Bei; Wu, Di; Qiu, Hong; Wang, Rongming
Abstract : Freestanding cathode materials with sandwich‐structured characteristic are synthesized for high‐performance lithium–sulfur battery. Sulfur is impregnated in nitrogen‐doped graphene and constructed as primary active material, which is further welded in the carbon nanotube/nanofibrillated cellulose (CNT/NFC) framework. Interconnected CNT/NFC layers on both sides of active layer are uniquely synthesized to entrap polysulfide species and supply efficient electron transport. The 3D composite network creates a hierarchical architecture with outstanding electrical and mechanical properties. Synergistic effects generated from physical and chemical interaction could effectively alleviate the dissolution and shuttling of the polysulfide ions. Theoretical calculations reveal the hydroxyl functionization exhibits a strong chemical binding with the discharge product (i.e., Li2 S). Electrochemical measurements suggest that the rationally designed structure endows the electrode with high specific capacity and excellent rate performance. Specifically, the electrode with high areal sulfur loading of 8.1 mg cm −2 exhibits an areal capacity of ≈8 mA h cm −2 and an ultralow capacity fading of 0.067% per cycle over 1000 discharge/charge cycles at C/2 rate, while the average coulombic efficiency is around 97.3%, indicating good electrochemical reversibility. This novel and low‐cost fabrication procedure is readily scalable and provides a promising avenue for potential industrial applications. Abstract : The rationally designed freestanding and sandwich‐structured electrode exhibits enhanced cycling stability with high specific capacity and high coulombic efficiency. This strategy achieves high level of optimization for electrochemical performance through hybridization‐combining multiple materials with unique characteristics within a single framework structure.